Identification of Protease-Producing Bacteria Isolated from Banyuwedang, Bali, and Characterization of its Protease - Zilda, Dewi Seswita; Fawzya, Yusro Nuri; Uria, Agustinus Robert (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2018)
Proteases or peptidases is known as a largest group of hydrolytic enzymes and have been applied in various industries such as food, pharmacy, leather, detergent and waste treatment. Although they are also produced by plants and animals, microbes remain the main source of proteases in the world market which mostly derived from Bacillus sp. Aims of this research were to identify isolate BII-1 and study its protease. Analysis of 16Sr RNA sequencing showed the identity of BII-1 as Bacillus subtilis (99% similarity with the same species in GenBank). It was found that protease from BII-1 exhibited optimal temperature and pH of 50 oC and 8-9, respectively. It was activated by Li2+, Na2+, Mg2+ and K+. The degenerated primer for protease gene was designed, and a partial protease gene was amplified from BII-1. The sequencing result showed that this amplified gene shared 100 and 99% similarity with those from Geobacillus thermophiles and Bacillus subtilis in the GenBank, respectively.Keywords: protease, bacteria, Bacillus subtilis, Geobacillus thermophylus